Analisis Konseptual Dasar Ilmu Pendidikan dalam Teori Pembelajaran Modern - Syafi'i, Muhammad Imam (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
Over the past few decades, existing learning theories have evolved rapidly, bringing about significant changes in the way education is understood and implemented. The aim of this research is to conceptually analyze the basic concepts of educational science, the implementation of modern learning theories, and the implications of applying modern learning approaches in the educational context. The approach method used in this research is a qualitative approach with a type of library research. The research results show that the basic science of education, which includes principles, theories, and fundamental concepts in education, plays a very important role in the development of modern learning theories. The implementation in the context of modern learning theory, the basic science of education guides the development of learning approaches and strategies that are more effective and relevant to the demands of today's society and technology. The implication is to help educators, policymakers, and educational practitioners design learning approaches that are more effective and relevant to today's context. This research provides a valuable contribution to understanding the complex relationship between the basic science of education and modern learning theory, as well as encouraging the development of educational science so that it remains relevant in facing changes in the dynamic world of education.